Propuesta de un manual de procesos y procedimientos del área de compras e inventarios de la comercializadora Mastercampo SAS (2022)
This graduation project was developed in order to carry out a Proposal for a Improvement of processes and procedures for the inventory control of the Comercializadora Mastercampo SAS, taking into account the internal control elements of the COSO II report.